A world history of war crimes : from antiquity to the present - Bryant, Michael S., 1962- (London, England : Zed Books, 2021)
"The greatly expanded and enhanced second edition of [this book] provides an authoritative and accessible global history of war crimes and the laws of war. Tracing human efforts to limit warfare, from codes of war in antiquity designed to maintain a religiously conceived cosmic order to the gradual use in the modern age of the criminal trial as a means of enforcing universal humanitarian norms, Michael Bryant's book is a masterful account of the subject. Five brand new chapters are included that reinforce the geographical, chronological, historiographical and conceptual dimensions of the book"--
The roots of the law of war in world history -- The law of war in pre-Columbian America -- Making law in the slaughterhouse of the world : early modernity & the law of war -- Colonialism and the law of war : Ireland and the Americas -- The law of war in eighteenth and nineteenth centuries : Europe and the United States of America -- The first world war and the failure of the law of war -- The second world war and the triumph of the law of war -- Into the 21st century : war crimes & their treatment since the second world war -- Singers of songs of experience : trying to explain war crimes in world history -- Conclusion : the future of the law of war.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: War crimes -- History; Crimes against humanity -- History; War (International law) -- History; General & world history; Electronic books